Experimental and numerical assessments of underlying natural air movement on PV modules temperature. (1st March 2021) - Naghavi, M.S.; Esmaeilzadeh, A.; Singh, B.; Ang, B.C.; Yoon, T.M.; Ong, K.S.
Highlights: The effect of the natural convection air movement is studied. The effect of distance between the panels and rooftop is studied. Experimental and numerical investigations were carried out. Temperature differences between no air gap and 200 mm air gap is about 12 ± 5 °C. Abstract: PV panel installation on rooftops is increasing all around the world. The negative effect of the temperature increment on the performance of the PV panels is known. This study aims to evaluate the effect of the gap between the panels and rooftop on the effectiveness of free natural convection to pick up heat from the PV panel. The experimental and numerical investigation was carried out to study the effect of the natural air movement beneath the five PV panels merged vertically. The scope of the study was limited to the temperature measurement of air inlet/outlet and PV panels temperature. The effect of distance between the panels and rooftop and the solar radiation intensity are two main parameters that were studied. The experimental and numerical results showed that the mean temperature of the PV array with no air gap could be about 12 ± 5 °C higher than one provided with an air gap greater than 200 mm and is about 18 ± 5 °C when the gap increased to 250 mm when the radiation is about 1000 W/m 2 . While the efficiency of the PV panel in STC is 18.04%, it drops to 14.17% when the gap is 0 mm and increases to 15.01% and 15.44% for the gaps of 200 mm and 250 mm. CFD simulation shows that surface temperatures of panels are nearly uniform. The CFD simulation follows the experimental results quite closely.